ANOMALI PASAR MODAL MENUJU STUDI BEHAVIORAL ECONOMICS - Andreas Kiky (Universitas Multimedia Nusantara, 2020)
Abstract- This research examine market anomali that used to be found in capital market. There are 3 (three) common market anomalies that observed by financial researcher, holiday effect (in this case Lebaran Effect), January effect and Monday effect. The goal in this empirical study is to confirm and examine these anomalies on consumer goods firms. One of most common misleading statement that would like to be argued by this research is on Lebaran Season; most likely consumer goods stocks would be the most wanted and highest return. Dummy variables are applied in research model to test research hypothesis regarding to this issue. Research models are analyzed using OLS approach and the result is indeed finding some anomali in Lebaran, January and Monday Effect. But the result from adjusted R2 is very low (<1%) which implies that explanatory power of event to abnormal return is need a critic and improvement. Further result from loss aversion theory confirms that most of Indonesian Citizen play save strategy under sure loss condition. Keywords: Capital Market Anomali, EMH, Lebaran Effect, January Effect, Monday Effect, Behaviour Economics